Pengaruh Dosis Pemupukan N terhadap Kualitas Biji Kakao di Punung Pacitan - Riris Rahayu Utami; Djoko Purnomo; Mercy Bientri Yunindanova (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
Punung is a village in Pacitan Regency which potentiall for cultivating of cocoa, on the contrary it produces low seeds quality. This condition is caused by unintensive fertilization and low light intensity caused by shading. The effort to increase cocoa seed quality was by light compensation and the use of nitrogen (N) fertilizer. The purpose of this reseach was to determine of optimum N dosage fertilizer for inproving seed quality. The research was arranged in Completely Randomized Block Design with one factor which is the varies N dosages (0 as control, 820, 870, and 920 gram plant-1 year-1), level of radiation represented as blocks. Nitrogen fertilization was applicated three times. Fertilization of P (SP36) and K (KCl), 1390 and 1000 gram tree-1 year-1 respectively. The observation variables are soil character, micro climate, leaf anatomi, physical and chemical seed quality. The result showed that N fertilizer influenced positively toward increasing potassium (K) content in leaf tissue on the first and second month, while on the third month no significant influence toward N, P and K content. However there was preference of increased N, P and K content in leaf tissue on each month although in small rise number. In the leaves tissue, there was detected that nitrogen proportion was larger than potassium and phosphorus. N fertilizer increased the physical and chemical seed quality (protein and fat content). Optimum dosage was 870 gram tree-1 year-1, highest weight of 100 seed (146 gram) and seed quality was categorized as grade 1.